2017
DOI: 10.1186/s12891-017-1802-z
|View full text |Cite
|
Sign up to set email alerts
|

Topical zoledronic acid decreases micromotion induced bone resorption in a sheep arthroplasty model

Abstract: BackgroundInitial micromotion of a total hip replacement is associated with aseptic loosening. The use of bisphosphonates could be one way to reduce peri-implant bone resorption induced by micromotion. Bisphosphonates compounds are inhibitors of bone resorption. The aim of this study was to investigate whether local treatment with bisphosphonate would reduce bone resorption and fibrous tissue around an experimental implant subjected to micromotion.MethodsOne micromotion implant were inserted into each medial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Implants can be used as fixation devices to stabilize fractures until they heal, and for prosthetic joint replacements to provide desired persistent osseointegration 2. Failure of prosthetic implant osseointegration will lead to early prosthetic implant migration, periprosthetic bone loss, localized bone lysis, and finally implant loosening, which may result in the need for revision 3,4. Periprosthetic bone loss, osteolysis, and subsequent loosening is by far the most common cause for revising total joint replacements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implants can be used as fixation devices to stabilize fractures until they heal, and for prosthetic joint replacements to provide desired persistent osseointegration 2. Failure of prosthetic implant osseointegration will lead to early prosthetic implant migration, periprosthetic bone loss, localized bone lysis, and finally implant loosening, which may result in the need for revision 3,4. Periprosthetic bone loss, osteolysis, and subsequent loosening is by far the most common cause for revising total joint replacements.…”
Section: Introductionmentioning
confidence: 99%
“…To address the issue of periprosthetic bone loss, research has recently been focused on the supplementary use of drugs that are known to influence bone turnover 1,2,4-6,8,12-15. Among these, bisphosphonates, through their antiresorptive properties on osteoclast activity, have demonstrated their ability to reduce the risk of hip and vertebral fractures and can have potential protective effects on implant survival 6,16.…”
Section: Introductionmentioning
confidence: 99%
“…Aseptic loosening is associated with peri-implant fibrous tissue formation, 2,3,[23][24][25][26] and early increased implant micromotion has been shown to result in fibrous tissue development around the implant. 27 Duyck et al 4 showed that micromotions exceeding 30 µm lead to impaired osseointegration and fibrous tissue formation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Increased early implant micromotion leads to the formation of periimplant fibrous tissue, a decrease in osseointegration, and ultimately impaired long-term implant survival. [2][3][4][5] Implant instability manifests radiologically as subsidence, radiolucency, and the formation of a pedestal, a new shelf of bone at the distal tip of the implant indicating distal load transfer. 6,7 High initial implant micromotion negatively influences osseointegration by applying shear stress on bone cells, influencing their activation and differentiation, and impacting the vitality of osteoblasts and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are the most commonly used materials for bone implants as they possess high mechanical strength, are anticorrosive, have a high elastic modulus and high biocompatibility, and are permissive to bone apposition owing to their bioinertness. , In addition, titanium-based implants have been shown to cause decreased fibrous tissue formation around the implant compared to other metals . Though joint replacement surgeries have a high rate of success, there is a need for revision surgery within the first 25 years after implantation in 20% of cases. , The most common cause for this implant failure is aseptic prosthetic loosening, and there have been several strategies aimed at avoiding this issue. ,, Implant failure can be the result of several contributing factors such as inadequate qualitative or quantitative bone stock, as well as age, gender, implant insertion trauma, and/or poor osseointegration. , For this work, we were focused on poor osseointegration as a contributing factor to aseptic prosthetic loosening …”
Section: Introductionmentioning
confidence: 99%